Some Fixed Points Results in b-Metric and Quasi b-Metric Spaces. (22nd January 2022) - George, Reny; Aranđelović, Ivan D.; Mišić, Vesna; Mitrović, Zoran D.
Abstract : We present a fixed point result in quasi b -metric spaces. Our result generalizes recent fixed point results obtained by Aleksić et al., Dung and Hang, Jovanović et al., Sarwar, and Rahman and classical results obtained by Hardy, Rogers, and Ćirić. Also, we obtain a common fixed point result in b -metric spaces. As a special case, we get a result of Ćirić and Wong.